2018
DOI: 10.1186/s40164-018-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of nivolumab in patients with advanced renal cell carcinoma treated in the United States

Abstract: BackgroundWe evaluated the cost-effectiveness of nivolumab versus everolimus in patients with advanced renal cell carcinoma (RCC) from a US payer perspective.MethodsA partitioned survival model consisting of three health states, progression-free survival (PFS), progressive disease, and death, was developed to evaluate the cost-effectiveness of intravenous nivolumab versus oral everolimus over a lifetime. The proportion of patients in each state was calculated based on parametric distributions fitted to PFS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…The results of one-way sensitivity analysis found that body weight had the greatest impact on the model outcome. One recent study that evaluated the cost-effectiveness of nivolumab versus everolimus in patients with advanced RCC in the US also found that average body weight had the greatest impact on the ICER for nivolumab versus everolimus (base case US $51,714; range US $8863–$94,566) [ 24 ]. The potential reason for this is that the dosage of sunitinib treatment is administered regardless of body weight, and the dosage of nivolumab and ipilimumab need to be adjusted according to the body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of one-way sensitivity analysis found that body weight had the greatest impact on the model outcome. One recent study that evaluated the cost-effectiveness of nivolumab versus everolimus in patients with advanced RCC in the US also found that average body weight had the greatest impact on the ICER for nivolumab versus everolimus (base case US $51,714; range US $8863–$94,566) [ 24 ]. The potential reason for this is that the dosage of sunitinib treatment is administered regardless of body weight, and the dosage of nivolumab and ipilimumab need to be adjusted according to the body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab and ipilimumab were administered intravenously at a dose of 3 mg/kg and 1 mg/kg, respectively, every 3 weeks for four doses (induction phase), followed by nivolumab monotherapy at a dose of 3 mg/kg every 2 weeks (maintenance phase). To calculate the dosage of nivolumab and ipilimumab agents, we assumed a typical patient weighed 71.4 kg in the US, 78.7 kg in the UK and 59 kg in China, and the range (29–112 kg) was used in the sensitivity analysis [ 16 , 24 , 25 ]. Based on previous reports, the maximum treatment duration of nivolumab plus ipilimumab was two years [ 16 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,[19][20][21][22][23][28][29][30][31][32] For dosage calculation in the United States and China, body surface area (BSA) and body weight of 1.84 m 2 , 71.4 kg and 1.72 m 2 , 65 kg were adopted respectively. [33][34][35]…”
Section: Health Care Resource Uses Costs and Utilitymentioning
confidence: 99%